Reinforced self-affirmation as a method of reducing the misinformation effect: Towards ecological validity - Szpitalak, Malwina (Psychology, crime & law, 2024)
The misinformation effect consists in the inclusion in witness testimonies of false information from sources other than the given event. Given that this is a serious threat for the quality of witness testimony, it is surprising that so little research has explored whether the influence of misinformation on remembering can be reduced. In this article, a method of enhancing self-confidence that is called reinforced self-affirmation (RSA) was shown to reduce the misinformation effect, which replicates previous research of this kind. RSA aims to boost self-confidence and consists of self-affirmation and manipulated positive feedback. In this article, the efficacy of RSA was explored in the context of initial testing, i.e. testing memory immediately after the original event, and several methods of activating self-affirmation and introducing positive feedback were tested. In general, RSA reduced the misinformation effect in all three experiments; however, it was not effective when initial testing was present, most probably due to ceiling effects caused by this testing.